Heart failure and cardiovascular outcomes in european patients with atrial fibrillation. (3rd October 2022) - Bonini, N; Proietti, M; Romiti, G F; Vitolo, M; Fawzy, A M; Ding, Y D; Fauchier, L; Marin, F; Nabauer, M; Potpara, T S; Dan, G A; Boriani, G; et al.
Abstract: Background: Heart failure (HF) has an intimate bidirectional association with atrial fibrillation (AF). Few data are available about the impact of HF phenotypes (HF with preserved ejection fraction, HFpEF; HF with mildly reduced ejection fraction, HFmrEF; HF with reduced ejection fraction, HFrEF) as predictors for adverse outcomes in AF patients. Purpose: To investigate the association of HFpEF, HFmrEF and HFrEF with adverse outcomes in a large contemporary cohort of European AF patients and evaluate the effect of EF throughout its entire spectrum. Methods: We analyzed patients enrolled in the ESC-EHRA EORP-AF General Long-Term Registry. HF patients were categorized according the three phenotypes and compared to those without HF ("non HF"). Main outcome was a composite outcome of all-cause death and major adverse cardiac events (MACE). Results: Among the original 11, 096 AF patients enrolled, 9857 (88.8%) were included in this analysis (median age 71 years, interquartile range [IQR 63–77], 40.1% females) with median EF 55% [IQR 45–61%] and CHA2DS2-VASc 3 [2–4]). In this cohort, 5935 (60.2%) were non HF patients, and 3240 (32.9%) had HF patients (with HF status and EF values data available). Accordingly, 1662 (51.2%) were categorized as HFpEF; 523 (14.1%) were HFmrEF; and 1235 (35.1%) were HFrEF. After a median follow-up of 731 days [IQR 690–748], the composite outcome was significantly higher throughout HF categories (HFpEF 19.0%, HFmrEF 21.8% and HFrEF 29.6%, compared to non HF 10.7%; p<0.001). In a fully adjusted multivariate Cox regression, HF phenotypes were associated with a progressively higher risk for the composite outcome (HFpEF HR 1.45 [95% CI, 1.23–1.70]; HFmrEF HR 1.82 [95% CI, 1.45–2.3]; HFrEF HR 2.51 [95% CI, 2.14–2.95], when compared to non HF patients). Considering EF in its continuous spectrum, an adjusted regression curve analysis found that progressively lower EF was associated with a progressively higher risk for the composite outcome, both in HF and overall AF patients (Figure 1, left and right panel, respectively). Conclusions: Over a two-years follow-up, in a large contemporary cohort of European AF patients, HF phenotypes were associated with a progressively higher risk for adverse outcomes. Lower EF values increased the risk of adverse outcomes both in HF patients and overall AF patients, irrespective of HF phenotype status. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2010–2021), and Vifor (2019–2022).